The Relationship Between Organisational Culture, Innovation, Competitive Intelligence Practices And Hotel Performance In Malaysia - Asri, Dian Aszyanti Atirah Mohd. (2023)
The hospitality industry is commonly acknowledged as a significant growth driver in modern economies. The hotel industry is one of the important sectors in the hospitality industry that contributes to the country’s revenue. This industry faces a critical challenge in retaining and attracting tourists due to several reasons involving spending patterns, the weak ringgit, and other economic pressures among domestic travellers. Apart from that, domestic travellers have shifted to cautious spending and prefer other accommodation providers, such as short-term accommodation, for their stay. Hotels are constantly changing their services and processes to accommodate changing tourist demands because of the dynamic competition imposed by globalisation. However, hotels must be versatile and innovative to meet a rising, volatile, and complex demand to remain competitive in today's rapidly changing markets, particularly because of the impacts of COVID-19. It is very crucial for the hotel industry to remain competitive and achieve higher performance in these turbulent times. Although the factors that influence hotel performance have been studied in the past, there are still critical issues that have not been thoroughly studied and need to be addressed. Drawing from Resource Based View (RBV) theory and Knowledge Based View (KBV) theory, the present study has objectives to examine (1) the relationship between clan, adhocracy, market and hierarchy culture towards innovation, (2) the relationship between innovation and hotel performance,